Dual-Stream MobileNetV2 and Light Mixer Fusion for Robust Weather Classification - Muhammad Reza Alfatah; Hadi Santoso (Peneliti Teknologi Teknik Indonesia, 2026)
This study proposes an image-based weather classification model designed to accurately recognize various sky conditions, with the aim of providing accessible weather information for elderly individuals and users with visual impairments. While existing lightweight models often struggle to effectively capture both fine-grained local textures and global contextual patterns, this study bridges the gap by proposing a hybrid dual-branch architecture. Specifically, the proposed model utilizes an early spatial feature-level fusion dual-branch architecture. The first branch combines MobileNetV2 with a Feature Pyramid Network (FPN) and incorporates selective attention mechanisms to capture multi-scale features. The second branch, referred to as the Mixer branch, improves visual feature representation through patch embedding and feature mixing techniques. Outputs from both branches are integrated using a fusion layer before being processed by a softmax classifier. The dataset includes five weather categories: cloudy, foggy, rainy, sunny, and sunrise, and is preprocessed through normalization, data augmentation, and partitioning into training, validation, and testing sets. Model training is conducted using TensorFlow and Keras with the Adam optimizer over a two-phase training schedule of 60 epochs (20 epochs for head-only pre-training and 40 epochs for whole-model fine-tuning). The experimental evaluation achieves a test accuracy of 0.975 (97.50%), with precision, recall, and F1-score reaching 0.976, 0.975, and 0.975, respectively, reflecting consistent and reliable classification performance. These results indicate that the proposed model has strong potential for integration with text-to-speech systems to improve accessibility of weather information for users with special needs.